Aplikasi Formulasi Kapur, Bahan Organik dan Pupuk NPK terhadap Kadar Aluminium dan Besi serta Pertumbuhan Jagung di Lahan Pasca-Tambang Batubara - Muhammad Hasan; Muhammad Syarbini; Bambang Joko Priatmadi (Acta Solum, 2023)
The level of solubility of aluminum and iron metals in the soil is one of the post-coal mining land problems. The high solubility of Al and Fe can be toxic to plants, so that plants are difficult to grow. This study aims to reduce the solubility of Al and Fe using formulations of liming, organic matter, and NPK fertilizer and to examine their effects on the growth and height of corn in post-coal mining land. The study used a Completely Randomized Design (CRD) with a single factor of ameliorant formulation. The treatment consisted of 10 treatments and was repeated three times, so there were 30 experimental units. The results showed that the application of ameliorant formulation of liming, organic matter, and NPK fertilizer had an effect on decreasing the solubility of Al and Fe in the soil and increasing the growth of corn in post-coal mining land. Soil that has been applied with K1 treatment (lime 3 t ha-1) can give the best results in reducing the solubility of Al and Fe metals in the soil. Application K2 treatment (giving organic matter 10 t ha-1), gave the best results for increasing the growth of corn in post-coal mining land. The best treatment for reducing Al and Fe soluble and increasing plant height growth was found in the treatment of lime 3 t ha-1 + organic matter 10 t ha-1 + NPK fertilizer 50 kg t ha-1, which was 0.42 (me 100g soil-1), 4.48 (ppm) and 108 (cm). The conclusion of this research is that the application of lime formulations, organic materials and NPK fertilizer is able to reduce levels of Al-dd, soluble Fe in the soil and increase the height growth of corn plants. Dolomite is able to reduce Al-dd and Fe-soluble levels. The application of organic and inorganic fertilizers affects the growth of corn height.